The Impact of Social Media as an Integral Communication Tool for Building Effective Teams - Adnan, Muhammad (Curtin University, 2021)
The current study aims to investigate the use of social media as a communication tool by students, applied within team-based environment using a quantitative empirical approach. Study focuses on creating groups and teams by using social media applications for use in the classrooms. Student participants from three international universities across Malaysia form the study participants. Data was collected using convenient sampling, which was then examined using correlation and descriptive analysis.